The Relationship Between Grade Configuration and Student Performance in Rural Schools - Bobby J. Franklin; Catherine H. Glascock (Journal of Research in Rural Education, 1998)
The purpose ofthis study was to examine the relationship between grade configuration-the sequence ofgrades in a school-and student behavior (attendance/suspensions) and academic achievement. Elementary (grades K-617), middle/ junior high (grades 617-8/9), secondary (grades 7/8/9-12), and unit (K-12) schools were examined using grade-level data at grades 6, 7, 10, and l l . Students in elementary and unit schools outperformed their middle and secondary school peers.